Implementation of Regional Tax Policies in Supporting PAD in Maybrat Regency, West Papua - Novalius Abraham Bleskadit; Sapto Pramono; Ika Devy Pramudiana (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to describe and analyze: the implementation of Regional Tax Policy in Supporting Regional Original Revenue in Maybrat Regency. And obstacles to the implementation of Regional Tax policies in supporting regional Original Revenue in Maybrat Regency. The research is a qualitative descriptive analysis. The data analysis technique uses a technique developed by McNabb (2002), namely Grouping the data according to key constructs, identifying bases for interpretation, developing generalizations from the data, Testing Alternative interpretations and Forming and/or refining generalizable theory from case study. The results of the study show that the Policy on Regional Taxes in Maybrat Regency is inseparable from the pattern of fiscal relations between the Central and Regional Governments. To increase PAD, the Maybrat Regency Government will apply taxpayers and levies comprehensively to all types of businesses in Maybrat Regency. This includes stalls, food stalls, shops, and building shops. In general, the policy of increasing Regional Original Revenue from the Regional Tax sector carried out by the Maybrat Regency Government is a policy in the form of intensification. Policy Implementation Implementation of Regional Tax Policies in Supporting PAD Maybrat Regency, West Papua includes communication carried out by the Maybrat Regency Dispenda, Maybrat Regency Government through socialization to OPDs, Village Heads of Business Actors in Maybrat Regency. The human resources owned by the Maybrat Regional Government are very limited. The disposition or attitude of policy implementers in Maybrat Regency is quite committed to increasing PAD through regional taxes. Bureaucratic structure. covering the dimension of standard operating procedures (SOP) realized through the Decree of the Regent of Maybrat Regent Number 61 of 2012 concerning the amount of tax collection and regional levies in Maybrat Regency. The obstacles faced include structural obstacles in the form of still the same level of echelonization between the Regional Original Revenue generating agencies and the Regional Revenue Office as the coordinator of the management of Regional Original Revenue, so that there are difficulties in coordinating the implementation of policies and reporting systems. Institutional constraints in the form of weak tax planning can be seen from the weak management of data collection and inventory of regional tax potential. Technical obstacles to the implementation of Regional Tax policies include limited facilities and capabilities for Regional Tax collectors and collectors. Non-technical obstacles to the implementation of Regional Tax policies are in the form of inadequate facilities and infrastructure.